2022
DOI: 10.1039/d2dt02623f
|View full text |Cite|
|
Sign up to set email alerts
|

Disentangling contributions to guest binding inside a coordination cage host: analysis of a set of isomeric guests with differing polarities

Abstract: Binding of a set of three isomeric guests (1,2-, 1,3- and 1,4-dicyanobenzene, abbreviated DCB) inside an octanuclear cubic coordination cage host H (bearing different external substitutents according to solvent used)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…This ratio is consistent with cavity binding, as the exterior surface is large enough to bind more than two guests [12a] . We also know from previous crystallographic studies that many small aromatic guests can bind inside the cavity of H as stacked pairs; [7,14a] and indeed the crystallographic studies discussed below, support formation of an H 1 :G 2 complex (see Figure 11). This guest binding mode is also in agreement with the outcome of the catalysis studies above, that concluded that 2 equivalents of the product DNP prevent the binding of DNFB and thereby inhibits the cage catalysed reaction (Figure 5).…”
Section: Resultssupporting
confidence: 83%
“…This ratio is consistent with cavity binding, as the exterior surface is large enough to bind more than two guests [12a] . We also know from previous crystallographic studies that many small aromatic guests can bind inside the cavity of H as stacked pairs; [7,14a] and indeed the crystallographic studies discussed below, support formation of an H 1 :G 2 complex (see Figure 11). This guest binding mode is also in agreement with the outcome of the catalysis studies above, that concluded that 2 equivalents of the product DNP prevent the binding of DNFB and thereby inhibits the cage catalysed reaction (Figure 5).…”
Section: Resultssupporting
confidence: 83%
“…1), based on hydroxymethyl-substituted bis-bidentate ligands (L W ) which span the edges of an approximately cubic array of Co(II) ions, can bind guests internally and externally and is also capable of binding multiple guests. [19][20][21][22] However, multiple guest binding has only been demonstrated using X-ray crystallography and NMR spectroscopy under forcing conditions with a large excess of guest. [19][20][21] Detailed MS studies, which are well suited to studying higher stoichiometry guest binding, have currently not been performed.…”
mentioning
confidence: 99%
“…1), based on hydroxymethyl-substituted bis-bidentate ligands (L W ) which span the edges of an approximately cubic array of Co(II) ions, can bind guests both internally and externally and is also capable of binding multiple guest. [13][14][15][16] However, multiple guest binding has only been demonstrated using X-ray crystallography and NMR spectroscopy under forcing condition with a large excess of guest. [13][14][15] Detailed MS studies, which are well suited to studying higher stoichiometry guest binding, have currently not been performed.…”
mentioning
confidence: 99%